THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM), BRAND IMAGE, AND PRICE ON RE-PURCHASE INTENTION OF AIRLINE CUSTOMERS - Arif, Moh Erfan (Universitas Brawijaya, Indonesia, 2019)
This research aims to investigate the factors which influence the Citilink customer's repurchase intention. This research implements Electronic Word of Mouth (eWOM), brand image, and price as the independent variables that influence customer's repurchase intention. This research applies explanatory research, and the data are collected by employing a survey method. The respondents comprised 180 customers who had purchased Citilink Indonesia minimum in one purchased. The research data and hypothesis are analyzed by using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Finally, the findings indicated that eWOM and brand image significantly and positively influence Citilink customer's repurchase intention. In conclusion, the more positive the eWOM from the Citilink Indonesia's previous customer, the higher the repurchase intention. In line with it, the more positive (good) brand image of Citilink Indonesia, the higher the repurchase intention of the customers.